R*-Small Submodules and -Hollow Modules - Jasim, Mustafa Mohammed; Khalid, Wasan (Iraqi Journal of Science, 2025)
The purpose  of this study is to present  a new concepts on a module M over a ring, these concepts is called R*-small sub module, R*-hollow module which present generalizations of the small submodule and hollow module, respectively. Key characteristics of these concepts such as the image and direct sum of R*-small sub module, R*-hollow module are R*-small submodule, R*-hollow submodule,  respectively.